If it's not what You are looking for type in the equation solver your own equation and let us solve it.
13y-12y=3
We move all terms to the left:
13y-12y-(3)=0
We add all the numbers together, and all the variables
y-3=0
We move all terms containing y to the left, all other terms to the right
y=3
| -14+y=-18 | | 6x/11=21 | | 7u-5u+2u+5u=18 | | 3=3z−15 | | y-8=-2;y=6 | | X^2/3=x/2 | | 3/10x+0.6=12 | | 2x+-1=-17 | | 6(u+5)=66 | | -1/8h=-2/7 | | 6y+2(y-5)=46 | | 6r+6=-6 | | 1/6=3x^2/2 | | 3x2+14x×16=0 | | x-11=123 | | 12.4+4x=62.4 | | 86=4x+2(1+5x) | | 1/6=3x2/2 | | 12x+5x-16x=12 | | X+0.1x=755.70 | | 8.05+-4j=12.05 | | 12/k=8/13 | | x+121+65=180 | | 2(9x+9)=8x | | 15/5=k/8 | | 9y=6=8y-2 | | 2.5h+10=4h+7 | | v/8-7=-5 | | -1.79+-4f=-17.79 | | 10a-26=8a-14 | | 3g+5=17.6 | | 12.5+4x=65.5 |